Productivity of Boran cattle maintained with chemoprophylaxis under high tsetse challenge at Mkwaja ranch in Tanzania. 1. Ranch organization and animal health management - Jibbo, J.M.C.; Trail, J.C.M.; Sones, Keith R.; Durkin, J.W.; Light, D.E.; Murray, M. (OAU/STRC, 1985)
Studies the productivity of Zebu cattle at Mkwaja ranch in Tanzania, upgraded by the importation of Boran bulls and semen from Kenya and maintained under the successful trypanocidal drug strategy; discusses the proper management of acaricides and anthelmintics, as well as bacterial and viral vaccines to keep the major infectious diseases on the ranch under control.